Scleroderma and malignancy: an epidemiological study. Issue 7 (July 1993) - Rosenthal, A K; McLaughlin, J K; Linet, M S; Persson, I
Abstract : OBJECTIVES--Although case reports and some patient series suggest an increased risk of cancer among patients with scleroderma, there are no population based studies to support this association. A population based follow up study was therefore carried out of 233 patients with scleroderma from the six-county Uppsala health care region of Sweden for the time period 1955-84. METHODS--Using the inpatient registry for the Uppsala health care region, all patients with scleroderma were identified. Their unique identification codes were then used to perform a record linkage with the National Cancer Registry. Expected cancer rates were determined using the age and gender specific rates for the Uppsala health care region. RESULTS--The standardised incidence ratio (SIR) for all cancers among these patients was significantly increased (SIR = 2.4; 95% CI = 1.5 to 3.6). The SIRs for lung cancer (SIR = 7.8; 95% CI = 2.5 to 18.2) and non-Hodgkin's lymphoma (SIR = 9.6; 95% CI = 1.1 to 34.5) were also significantly increased. Excluding patients who were diagnosed with cancer within a year of their scleroderma diagnosis resulted in similar findings, though the SIR for non-Hodgkin's lymphoma was no longer statistically significant. CONCLUSIONS--Larger population based investigations of cancer risk among patients with scleroderma are needed to confirm these initial findings and to evaluate in greater detail possible cancer risk among these patients.